Crack investigation by employing finite element method with fuzzy logic tool for a steel cantilever rod - Hameed Rasheed, Hind; M, Ashham; K, Salman (International Journal of Engineering and Technology, 2019)
The present study is aiming to investigate crack presence in the rigid steel beam in order to take this in account in structural design .FEM has been used in ANSYS software to simulate whole steel body with three different frequencies with a magnitude force that subjected at the free end of the beam. Furthermore MATLAB has been conducted to find the crack by employing Fuzzy Logic. Both approach s has been governed by The Euler- Bernoulli theory for free vibration for motion equations. As well as the other main target of this study to evaluate results that has been got by ANSYS software with MATLAB coding for the same boundary conditions of the case.Â